THE EFFECT OF THE JIGSAW TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS VIII STUDENTS AT SMP NEGERI 2 WAINGAPU - Karolina Konga Wandal; Yohana Makaborang; Yohana Ndjoeroemana (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of the Jigsaw Cooperative Learning Model on the Learning Outcomes of Class VIII Students at SMP Negeri 2 Waingapu. This type of research is a quasi-experimental research design using nonequivalent control group design. Sampling using purposive sampling. The population in this study were class VIIIE students at SMP Negeri 2 Waingapu in the odd semester of 2022/2023. The sample of this research is 32 students of class VIIIE as an experimental class. The results of the descriptive analysis obtained showed that the pretest and posttest scores for the experimental class were 69.19 <76.28 while the pretest and posttest scores for the control class were 63.50 <69.56. Further testing the hypothesis using the paired sample t-test produces an Asymp value. Sig (2-tailed) 0.000 means that the value is less than 0.05 (< 0.05). It can be concluded that the Jigsaw cooperative learning model has an influence on learning outcomes.Keywords: Learning Model, Cooperative, Jigsaw Type, Learning OutcomeAbstrakPenelitian ini bertujuan untuk mengetahui Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Kelas VIII di SMP Negeri 2 Waingapu. Jenis penelitian ini adalah kuasi eksperimen menggunakan desain penelitian nonequivalent control group design. Pengambilan sampel menggunakan purposive sampling. Populasi pada penelitian ini adalah peserta didik kelas VIIIE di SMP Negeri 2 Waingapu pada semester ganjil 2022/2023. Sampel penelitian ini yaitu 32 peserta didik kelas VIIIE sebagai kelas eksperimen. Hasil analisis deskriptif yang diperoleh menunjukkan bahwa nilai pretest dan posttest kelas eksperimen 69,19 < 76,28 sedangkan nilai pretest dan posttest kelas kontrol 63,50 < 69,56. Lebih lanjut pengujian hipotesis menggunakan uji paired sample t-test menghasilkan nilai Asymp. Sig (2-tailed) 0,000 artinya nilai tersebut kurang dari 0,05 (< 0,05). Dapat disimpulkan bahwa model pembelajaran kooperatif tipe Jigsaw memiliki pengaruh terhadap hasil belajar.Kata kunci: Model Pembelajaran, Kooperatif, Tipe Jigsaw, Hasil Belajar